Herbal Medicine “Shulifenxiao” Formula for Nephrotic Syndrome of Refractory Idiopathic Membranous Nephropathy - Cui, Hailan; Fu, Frank Qiang; Liu, Baoli; Liu, Wei Jing; Liu, Yu Ning (Frontiers in Pharmacology, 2021)
Background: Treatment for adult patients with refractory membranous nephropathy (RMN) by conventional immunosuppressive regimens is not satisfactory. This study aims to evaluate the effectiveness of Chinese herbal medicine, Shulifenxiao formula, as a promising regimen. Methods: A total of 31 RMN patients resistant to corticosteroid or immunosuppressive agents were retrospectively analysed. Shulifenxiao treatment lasted a minimum of 12 months in all patients and extended to 24 months in 11 patients. The primary outcomes (the complete remission (CR) and partial remission (PR)) and secondary outcomes (the serum creatinine and estimated glomerular filtration rate (eGFR) levels) were measured at 6, 12, 18, and 24 months. Results: The data provided an average follow-up of 21±9.16 months from baseline. The remission was attained in 25/31 patients (80.7%: CR 29.0% and PR 51.6%) at 12 months and in 10/11 patients (90.9%: CR 54.6% and PR 36.4%) at 24 months, respectively. Proteinuria reduced from 6.02 g/d at baseline to 0.98g/d at 12 months (P<0.001) and to 0.27g/d at 24 months (P=0.003); serum albumin increased from 28 g/L to 37.2g/L at 12 months (P<0.001) and to 41.3g/L at 24 months (P=0.003); eGFR improved from 100.25 mL/min/1.73m² to 118.39mL/min/1.73m² at 6 months (P<0.001) and finally to 111.62mL/min/1.73m² at 24 months (P=0.008). Only two patients developed subsequent relapse. Conclusions: Shulifenxiao formula as a clinical cocktail therapy serves as an alternative therapeutic option for steroid and immunosuppressant-resistant RMN patients, with a favourable safety profile, though further studies are warranted.